Effect of potassium on yield and some qualitative and physiological traits of safflower (Carthamus tinctorius L.) under drought stress conditions. (15th June 2023) - Kikhazaleh, Mehdi; Ramroudi, Mahmoud; Galavi, Mohammad; Ghanbari, Seid Ahmad; Fanaei, Hamid Reza
Abstract: Improving the pattern of water consumption in the agricultural sector is one of the necessary measures to manage the water crisis in the country. The present study was conducted to investigate the effects of drought stress on yield and physiological characteristics of safflower under different amounts of potassium fertilizer. The experiment was performed as a combined analysis in a randomized complete block design with three replications during 2018 and 2019. The main plot consisted of drought stress at three levels of 45%, 65%, and 85% of permissible moisture drain and the subplot consisted of potassium fertilizer at four levels of zero, 75, 150, and 225 kg of potassium sulfate per hectare. In the second year compared to the first year, the amount of proline and seed oil were significantly higher by 23.4% and 4.43%, respectively, and the amount of carbohydrates and chlorophyll a were significantly lower by 11.9% and 27.4%, respectively. With increasing potassium intake, the amount of chlorophyll a increased significantly, and the highest amount of chlorophyll a at the rate of 16.7 mg/L was obtained in the treatment of 225 kg of potassium per hectare. With increasing the intensity of stress from 45% to 85% of moisture drain in different levels of potassium fertilizer, seed yield decreased significantly. Treatment of 85% moisture drain in no application of potassium showed the highest amount of proline. The application of potassium is effective in modulating the negative effects of drought stress on seed yield, qualitative, and physiological characteristics of safflower.